Impact that lack of knowledge can have on type 2 Diabetes Mellitus (Research, Society and Development, 2023)
Diabetes mellitus is a metabolic disease, considered a global health problem, affecting approximately 422 million people worldwide. The incidence of diabetes mellitus has increased in a worrying way, related to genetic factors, lifestyle habits and lack of knowledge about the pathology. Thus, the objective of this article is to develop an integrative review regarding the impact that the lack of knowledge has on Type 2 Diabetes mellitus, analyzing the natural evolution of the disease, transmitting knowledge and awakening diligence in nursing professionals. It is a narrative bibliographical research, formulation of the problem question: “What impacts can the lack of knowledge about Type 2 Diabetes mellitus have on the health of the Brazilian population?”. That knowledge is essential for permanence and adherence to the pathology, in which the patient has informational resources to know how the disease acts, the self-care method, which consists of drug treatment and non-drug treatment and the prevention of complications. The importance of the multidisciplinary team, emphasizing the Nurse for having panoramic knowledge and the ability to act in this area as an educator, solving the patient's doubts and methodically contributing with new information, that is, with health education, the user has one more resource to deal with with your disease and have quality of life.